Estimating the COGARCH(1,1) model: a first go - Stephan Haug; Claudia Klüppelberg; A. Lindner; M. Zapp (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2005)
We suggest moment estimators for the parameters of a continuous time GARCH(1,1) process based on equally spaced observations. Using the fact that the increments of the COGARCH(1,1) process are ergodic, the resulting estimators are consistent. We investigate the quality of our estimators in a simulation study based on the compound Poisson driven COGARCH model. The estimated volatility with corresponding residual analysis is also presented.
urn:nbn:de:bvb:19-epub-1827-8
Keywords: C23; C52; 519; continuous time GARCH process; GARCH process; Lévy process; moment estimators; stochastic volatility; volatility estimation